Serology, molecular and bacteriology of Leptospira spp. among humans and animals in Southeast Asia from 2011-2021: a review - Khor, Kuan Hua; Lau, Seng Fong; Muhd, Z. (Malaysian Veterinary Medical Association, 2024)
Leptospirosis is a bacterial disease caused by pathogenic Leptospira spp. As a zoonotic disease, it can be passed from animals to humans, causing infection in humans. However, a comprehensive compilation of serovars' diagnosis and distribution among infected hosts is still lacking. This review summarised these aspects within Southeast Asia to guide future studies and prevention efforts in the region. The database search was conducted from January 2011 to January 2021 using Scopus, PubMed, and Google Scholar. Studies on leptospirosis from all 11 Southeast Asia countries (Brunei, Burma/ Myanmar, Cambodia, Indonesia, Laos, Malaysia, Philippines, Singapore, Thailand, Timor Leste, and Vietnam) were obtained during this search. Data related to leptospirosis, including serovar types, human and animal infections, and diagnostic methods, were extracted from relevant studies. The 155 studies reported in Southeast Asia originated from Cambodia, Indonesia, Laos, Malaysia, Philippines, Thailand, and Vietnam. A total of 155 studies consisted of multiple tests: 87.1% (135/155) studies employed serological tests, with 71% (110/155) studies that reported serovars; 65.2% (101/155) studies used molecular tests; and 30.3% (47/155) studies utilised culture methods. The presence of circulating serovar within these countries indicates an endemic re-emerging disease. This review highlights the potential for various host species to become infected and act as carriers of leptospirosis. The importance of circulating serovars in epidemiological studies should be further investigated. There is an urgent need for intervention and the development of improved diagnostic strategies, particularly in low-income countries.